Plate 107: Device for two men to drain water from a marsh or foundation - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
Mechanics: hand crank; swinging-vane rotary pump; spur gear and lantern.
Keywords: Pumping machinery; Rotary pumps; Machinery; Hand pumps